FLUKTUASI DAN DISPARITAS HARGA BAHAN PANGAN POKOK DI WILAYAH TERTINGGAL, TERPENCIL, TERLUAR, DAN PERBATASAN DI MALUKU UTARA DAN PAPUA BARAT YANG DILALUI PROGRAM TOL LAUT - Prasetyo, Leo Bambang Budi; Armijaya, Henry; Purwanti, Oka; Firman, Achmad (Universitas Galuh, 2023)
The government is trying to improve food distribution routes to underdeveloped, remote, outermost and border areas through the Sea Highway program. The purpose of this study was to analyze fluctuations and disparities in food prices in Tidore District, North Maluku Province and Bintuni Regency, West Papua Province. This research was conducted through a price survey in the city of Surabaya as the initial area for the distribution of food goods through the port of Tanjung Perak to the port of Ternate (North Maluku) and the port of Sorong (West Papua). The samples taken were wholesalers in Surabaya City and retail traders in Tidore and Bintuni Regencies. The results of the study show that chillies are a commodity that experiences price fluctuations both in Tidore Regency, North Maluku and Bintuni Regency, West Papua. As for chilies and cooking oil, there is a high price disparity in Tidore Regency, North Maluku, while purebred chicken meat is a commodity that experiences price disparities in the West Papua region